A Nonlinear Unit Root Test in the Presence of an Unknown Break - Stephan Popp (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
The Perron test is the most commonly applied procedure to test for a unit root in the presence of a structural break of unknown timing in the trend function. Deriving the Perron-type test regression from an unobserved component model, it is shown that the test regression in fact is nonlinear in coefficient. Taking account of the nonlinearity leads to a test with properties that are exclusively assigned to Schmidt-Phillips LM-type unit root tests.
Keywords: C12; C22; 330; Unit root tests; nonlinear regression; structural breaks; innovational outliers; Unit Root Test; Regression; Strukturbruch; Nichtlineares Verfahren; Theorie